2013
DOI: 10.1128/mmbr.00056-12
|View full text |Cite
|
Sign up to set email alerts
|

Role of Factor H Binding Protein in Neisseria meningitidis Virulence and Its Potential as a Vaccine Candidate To Broadly Protect against Meningococcal Disease

Abstract: SUMMARY Neisseria meningitidis is a Gram-negative microorganism that exists exclusively in humans and can cause devastating invasive disease. Although capsular polysaccharide-based vaccines against serogroups A, C, Y, and W135 are widely available, the pathway to a broadly protective vaccine against serogroup B has been more complex. The last 11 years has seen the discovery and development of the N. meningitidis serogroup B (MnB) outer membrane protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
82
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 134 publications
(229 reference statements)
0
82
0
Order By: Relevance
“…B24 is found in 43.8% and 16.7% of invasive NmB strains in the USA and Europe, respectively (13). Thus, additional non-fHbp components were included in Bexsero to extend the coverage of the vaccine to other strains (14). Trumenba contains two lipidated fHbp variants, one from subfamily A (variant A05) and one from subfamily B (variant B01).…”
Section: Introductionmentioning
confidence: 99%
“…B24 is found in 43.8% and 16.7% of invasive NmB strains in the USA and Europe, respectively (13). Thus, additional non-fHbp components were included in Bexsero to extend the coverage of the vaccine to other strains (14). Trumenba contains two lipidated fHbp variants, one from subfamily A (variant A05) and one from subfamily B (variant B01).…”
Section: Introductionmentioning
confidence: 99%
“…This vaccine is licensed in the European Union, Australia, and Canada. Another serogroup B vaccine that contains FHbp is in late-stage clinical development by Pfizer Vaccines (2). FHbp was referred to as GNA 1870 (3) or LP2086 (4) when our laboratories discovered that an important function of this protein was to bind complement factor H (FH) to the bacterial surface and downregulate complement activation (5).…”
mentioning
confidence: 99%
“…Estimating the breadth of strain coverage afforded by the bivalent rLP2086 vaccine is a complex task, but, using a methodology based on a killing assay, it has been reported that for toddlers and adolescents-young adults, protective bactericidal titers ranged from 44% to 100% and from 68% to 98%, respectively, against MenB strains expressing heterologous fHbp proteins (17).…”
mentioning
confidence: 99%